Navigating Cross-Cultural and Religious Educational Contexts: American EFL Teachers in Indonesian Madrasahs - Ria Fakhrurriana; Anwarul Mustofa; Griselda Gian Heris Herdina (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
The increasing involvement of foreign English as a Foreign Language (EFL) teachers in Indonesian educational institutions has raised questions regarding how they adapt to culturally and religiously distinctive learning environments such as madrasahs. While previous studies have discussed cross-cultural teaching experiences, limited attention has been given to how foreign teachers navigate pedagogical and religious dimensions within Indonesian Islamic schools. Therefore, this study aims to examine the challenges and opportunities experienced by American EFL teachers teaching in Indonesian madrasahs. This research employed a qualitative approach using an exploratory collective case study design. Six American teachers from different madrasahs in Indonesia participated in the study. Data were collected through semi-structured interviews supported by reflective teaching notes and teaching materials and analysed using thematic analysis. The findings revealed that participants experienced challenges related to curriculum differences, classroom interaction, communication styles, cultural adaptation, and the integration of religious values into teaching practices. However, these challenges also created opportunities for professional and personal growth through collaboration with local teachers and engagement with the socio-religious environment of madrasahs. The study demonstrates that successful teaching in faith-based educational settings requires not only linguistic competence but also intercultural competence, cultural humility, adaptive pedagogy, and religious literacy. These findings highlight the importance of institutional support, intercultural preparation, and collaborative teaching practices to improve foreign teachers’ adaptation and effectiveness in religious educational contexts.